Developing A General Algorithm For Ball CurveWith GC2. - R., Gobinathan; O., Norziah; Md. Ali, Jamaludin (2005)
This paper dwells in developing a general algorithm for constructing a piecewise Ball Curve with curvature continuity (GC2).